The Apostle Paul and his letters : an introduction - Prothro, James B., 1986- (Verbum domini, 2021)
"The letters of the Apostle Paul are central witnesses to the Christian faith and to the earliest history of Christianity. And yet, when students, preachers, and others turn to Paul, they find many things "hard to understand" (2 Peter 3:16) in these ancient writings. This book offers an introduction for those who study, teach, and preach these biblical books. Steeped in up-to-date scholarship and a passion for the gospel Paul preached, Prothro draws readers into Paul's life and letters in order to help them hear the Apostle's voice. The book's chapters offer introductions to Paul's background, life, and legacy; each includes the following: an introduction to ancient letter writing; a guide to understanding Paul's theology across the letters; a survey of the portrait of Paul in the Book of Acts; separate treatments of each letter's background and purpose; treatments of key theological topics in each letter; a thorough outline of each letter showing its arguments and how they make sense. Prothro not only offers answers but models how to ask questions, helping us reason through Paul's letters as ancient documents and as Christian Scripture"--